Teaching Foreign Languages in Higher Education Institutions in Uzbekistan (Eurasian Research Bulletin, 2022)
After gaining our Independence, today, while implementing the reforms of preparing cadres, all new specialists undergoing the higher educational system are required to know one or several foreign languages. In connection with this, huge tasks are set before teachers of English language; teachers became one of the main subjects of educational reforms. Therefore, if a teacher is open to welcome new pedagogical innovations, he can provide goal-oriented introduction of innovative ideas into educational process. English is one of the main subjects being offered in the Uzbek education system and being taught in primary, secondary schools and higher educational establishments.